Sleep Disturbance, Sleep Duration, and Inflammation: A Systematic Review and Meta-Analysis of Cohort Studies and Experimental Sleep Deprivation - Irwin, Michael R. (Biol Psychiatry, 2015)
BACKGROUND: Sleep disturbance is associated with inflammatory disease risk and all-cause mortality. Here, we assess global evidence linking sleep disturbance, sleep duration, and inflammation in adult humans. METHODS: A systematic search of English language publications was performed, with inclusion of primary research articles that characterized sleep disturbance and/or sleep duration or performed experimental sleep deprivation, and assessed inflammation by levels of circulating markers. Effect sizes (ES) and 95% confidence intervals (CI) were extracted and pooled using a random effect model. RESULTS: A total of 72 studies (n>50000) were analyzed with assessment of C-reactive protein (CRP), interleukin-6 (IL-6), and tumor necrosis factor α (TNF). Sleep disturbance was associated with higher levels of CRP (ES 0.12; 95% CI 0.05 – 0.19) and IL-6 (ES 0.20; 95% CI 0.08 – 0.31). Shorter sleep duration, but not the extreme of short sleep, was associated with higher levels of CRP (ES 0.09; 95% CI 0.01 – 0.17) but not IL-6 (ES 0.03; 95% CI −0.09 – 0.14). The extreme of long sleep duration was associated with higher levels of CRP (ES 0.17; 95% CI 0.01 – 0.34) and IL-6 (ES 0.11; 95% CI 0.02 – 0.20). Neither sleep disturbances nor sleep duration was associated with TNF. Neither experimental sleep deprivation nor sleep restriction was associated with CRP, IL-6, or TNF. Some heterogeneity among studies was found, but no evidence of publication bias. CONCLUSIONS: Sleep disturbance and long sleep duration, but not short sleep duration, are associated with increases in markers of systemic inflammation.